Process for the preparation of high molecular weight hydrogenated bisphenol a polycarbonate and its use

CN117567734BActive Publication Date: 2026-10-16CHANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311379173.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-24
Publication Date
2026-10-16
Estimated Expiration
2043-10-24

AI Technical Summary

Technical Problem

由于目前工艺合成的HBPA-PC分子量较低,需要寻找高效的催化剂和合成工艺,来提高分子量,并有望进一步提高HBPA-PC的机械性能

Benefits of technology

[0026](1) The preparation method of the present invention is simple in operation; the hydrogenated bisphenol A type polycarbonate prepared has a conversion rate of up to 97.6%, a weight-average molecular weight of 30,000, an intrinsic viscosity of 0.45 dL/g, a tensile strength of 15.6 MPa, and a glass transition temperature of up to 178℃, and has good heat resistance; the film prepared by it has a light transmittance of 98.2% and a refractive index of 1.6385 at a wavelength of 1550 nm, and has a good application prospect in the field of polyester film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117567734B_ABST
    Figure CN117567734B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of high-molecular-weight hydrogenated bisphenol A polycarbonate. In a nitrogen atmosphere, hydrogenated bisphenol A, diphenyl carbonate and an organic alkali catalyst are added into a reaction kettle, stirring is started and temperature is raised to 180-210 DEG C, vacuum is extracted to 5-20 KPa to remove by-product phenol; then, temperature is continuously raised to 210-250 DEG C, vacuum is extracted to below 1 KPa to carry out polycondensation reaction, and after the reaction is finished, hydrogenated bisphenol A polycarbonate is obtained by cooling. The preparation method has simple operation process and high conversion rate. The hydrogenated bisphenol A polycarbonate prepared by using the organic alkali catalyst has a specific viscosity of 0.45 dL / g, a weight average molecular weight of 30,000, a molecular weight distribution of below 1.5, a tensile strength of 15.6 MPa, a glass transition temperature of 178 DEG C and good heat resistance; the prepared film has a light transmittance of 98.2%, a refractive index of 1.6385 at a wavelength of 1550 nm and a good application prospect in the polyester film field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polycarbonate preparation, specifically relating to a method for preparing high molecular weight hydrogenated bisphenol A type polycarbonate and its application. Background Technology

[0002] Hydrogenated bisphenol A polycarbonate (HBPA-PC) is a polymer material synthesized from hydrogenated bisphenol A and diphenyl carbonate through esterification and condensation polymerization. Compared with bisphenol A PC, HBPA-PC, due to its cyclohexane structure, is harmless to the human body, has good UV resistance, and high rigidity, making it promising for applications in medical devices, electronics, and automotive parts. However, currently reported HBPA-PCs have low molecular weights and poor mechanical properties, limiting their practical application.

[0003] There are few reports on HBPA-PC in the literature. It is mainly synthesized by melt esterification, using catalysts such as organotin oxide, 4-dimethylaminopyridine or lithium chloride. Xia Ranran et al. used organotin oxide as a catalyst to catalyze the synthesis of HBPA-PC from hydrogenated bisphenol A and dimethyl carbonate, with a conversion rate of 84.0% and a weight-average molecular weight of 6500 (Xia Ranran, Li Zhenhuan, Cheng Bowen, Su Kunmei, The structure of organotin oxide plays a key role in the transesterification reaction of dimethyl carbonate and hydrogenated bisphenol A. Korean Journal of Chemical Engineering, 2014, 31(3):427-430). Gan Yun synthesized HBPA-PC by adding 4-dimethylaminopyridine as a catalyst to hydrogenated bisphenol A and diphenyl carbonate. The reaction time was 7 hours and the weight-average molecular weight was only 5500 (Gan Yun, Research on hydrogenated bisphenol A type epoxy resin and polycarbonate, Nanjing University, 2014). Lu Wenfang et al. used lithium chloride as a catalyst to catalyze the hydrogenation of bisphenol A and diphenyl carbonate to synthesize HBPA-PC. The glass transition temperature was 160℃, and the weight-average molecular weight was only 15800 (Lu Wenfang, Zhang Ming, Wu Guozhang, Synthesis of hydrogenated bisphenol A type polycarbonate by melt transesterification, Journal of East China University of Science and Technology, 2019, 45(6):868-872). Since the molecular weight of HBPA-PC synthesized by the current process is low, it is necessary to find efficient catalysts and synthesis processes to increase the molecular weight, and it is expected to further improve the mechanical properties of HBPA-PC. Summary of the Invention

[0004] The purpose of this section is to outline some aspects of embodiments of the present invention and to briefly describe some preferred embodiments. Simplifications or omissions may be made in this section, as well as in the abstract and title of this application, to avoid obscuring the purpose of these documents; however, such simplifications or omissions should not be construed as limiting the scope of the invention.

[0005] Gan Yun explored the preparation method of HBPA-PC, synthesizing bisphenol A type polycarbonate (HBPA-PC) via transesterification polycondensation. Using di-tert-butyl instead of the conventionally used diphenyl carbonate to synthesize the polycarbonate prepolymer, the interpolymerization or self-polymerization between the polycarbonate prepolymer and hydrogenated bisphenol A only yielded HBPA-PC with a weight-average molecular weight of only 5500. (Gan Yun, Research on Hydrogenated Bisphenol A Type Epoxy Resin and Polycarbonate, Nanjing University, 2014)

[0006] Lu Wenfang et al. used lithium chloride as a catalyst to catalyze the synthesis of HBPA-PC with a molecular weight of only 15,800 from hydrogenated bisphenol A and diphenyl carbonate. (Lu Wenfang, Zhang Ming, Wu Guozhang, Synthesis of hydrogenated bisphenol A type polycarbonate by melt transesterification, Journal of East China University of Science and Technology, 2019, 45(6):868-872)

[0007] Wang Jin used a nitrogen-purging process with LiOH as a catalyst to melt-exchange DPC with HBPA, synthesizing only HBPA–PC prepolymer. The intrinsic viscosity was only 0.15 dL / g, and the weight-average molecular weight was low. (Wang Jin, Synthesis of Polycarbonate Prepolymer by Melt-Exchange Method, Engineering Plastics Application, 2021, 49(10):39-43.)

[0008] In view of the problems existing in the above and / or prior art, the present invention is proposed.

[0009] Therefore, the purpose of this invention is to overcome the shortcomings of the prior art and provide a method for preparing high molecular weight hydrogenated bisphenol A type polycarbonate.

[0010] To solve the above-mentioned technical problems, the present invention provides the following technical solution: a method for preparing high molecular weight hydrogenated bisphenol A type polycarbonate, characterized in that it includes,

[0011] Under a nitrogen atmosphere, hydrogenated bisphenol A, diphenyl carbonate and organic base catalyst were added to the reactor and stirred. During the esterification stage, the temperature was increased and a vacuum was drawn to continuously remove the byproduct phenol. During the polycondensation stage, the temperature was increased and a vacuum was drawn to carry out the polycondensation reaction. After the reaction was completed, the reactor was cooled to obtain hydrogenated bisphenol A type polycarbonate.

[0012] The hydrogenated bisphenol A type polycarbonate has the following structural formula:

[0013]

[0014] Where n is a positive integer.

[0015] In a preferred embodiment of the preparation method described in this invention, the organic base catalyst is at least one selected from potassium methoxide, lithium methoxide, potassium acetate, sodium acetate, and lithium acetate.

[0016] In a preferred embodiment of the preparation method described in this invention, the molar ratio of hydrogenated bisphenol A to diphenyl carbonate is 1:0.95 to 1.15; and the molar ratio of hydrogenated bisphenol A to catalyst is 1:0.01% to 0.5%.

[0017] In a preferred embodiment of the preparation method described in this invention, the hydrogenated bisphenol A and diphenyl carbonate are used as raw materials to synthesize polycarbonate, and the transesterification reaction time is 0.5 to 12 hours.

[0018] In a preferred embodiment of the preparation method described in this invention, the esterification stage is heated at a temperature of 180–210°C, and the polycondensation stage is heated at a temperature of 210–250°C.

[0019] In a preferred embodiment of the preparation method described in this invention, the vacuum degree of the esterification stage is 5-20 kPa; the vacuum degree of the polycondensation stage is below 1 kPa.

[0020] In a preferred embodiment of the preparation method described in this invention, the stirring speed is 10–500 r / min.

[0021] As a preferred embodiment of the preparation method described in this invention, the prepared hydrogenated bisphenol A type polycarbonate has an intrinsic viscosity of 0.45 dL / g, a weight-average molecular weight of 30,000, a molecular weight distribution of less than 1.5, a tensile strength of 15.6 MPa, and a glass transition temperature of 178°C.

[0022] As a preferred embodiment of the preparation method described in this invention, the film prepared from hydrogenated bisphenol A type polycarbonate has a light transmittance of 98.2% and a refractive index of 1.6385 at a wavelength of 1550 nm.

[0023] Another objective of this invention is to overcome the shortcomings of the prior art and provide a method for preparing high molecular weight hydrogenated bisphenol A type polycarbonate.

[0024] Another objective of this invention is to overcome the shortcomings of the prior art and provide a method for preparing high molecular weight hydrogenated bisphenol A type polycarbonate for the application of products obtained in electronic appliances, medical devices, and automotive parts.

[0025] Beneficial effects of this invention:

[0026] (1) The preparation method of the present invention is simple in operation; the hydrogenated bisphenol A type polycarbonate prepared has a conversion rate of up to 97.6%, a weight-average molecular weight of 30,000, an intrinsic viscosity of 0.45 dL / g, a tensile strength of 15.6 MPa, and a glass transition temperature of up to 178℃, and has good heat resistance; the film prepared by it has a light transmittance of 98.2% and a refractive index of 1.6385 at a wavelength of 1550 nm, and has a good application prospect in the field of polyester film.

[0027] (2) This invention uses an organic base catalyst to catalyze the hydrogenation of bisphenol A and diphenyl carbonate to synthesize HBPA-PC. The reaction process is simple to operate, with a conversion rate of up to 97.6% and a short reaction time. The obtained HBPA-PC has a weight-average molecular weight of 30,000, an intrinsic viscosity of 0.45 dL / g, a tensile strength of 15.6 MPa, and a glass transition temperature of up to 178℃, which has good application prospects. Attached Figure Description

[0028] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort. Wherein:

[0029] Figure 1 The infrared spectrum of HBPA-PC-1.

[0030] Figure 2 The image shows the proton NMR spectrum of HBPA-PC-1.

[0031] Figure 3 The differential scanning calorimetry curve for HBPA-PC-1 is shown.

[0032] Figure 4 This is a thermogravimetric analysis diagram of HBPA-PC-1.

[0033] Figure 5 This is a schematic diagram of powder diffraction for HBPA-PC-1.

[0034] Figure 6 Vicat softening point diagrams for HBPA-PC with different intrinsic viscosities.

[0035] Figure 7 This is a diagram of a hot-pressed film made of HBPA-PC using a flat vulcanizing machine. Detailed Implementation

[0036] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the examples in the specification.

[0037] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.

[0038] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that is mutually exclusive with other embodiments.

[0039] Example 1

[0040] In a 100 mL three-necked flask equipped with a nitrogen inlet, a by-product distillation outlet, and a mechanical stirrer, hydrogenated bisphenol A (12.02 g, 0.05 mol), diphenyl carbonate (11.25 g, 0.0525 mol), and potassium methoxide (3.5 mg, 0.05 mmol) were added. The reaction mixture was stirred and heated to 210 °C, and reacted under a vacuum of 5 kPa for 1 hour. The temperature was then increased to 230 °C while the vacuum was decreased to 0.1 kPa. The reaction was stopped when the rod-climbing phenomenon occurred, yielding hydrogenated bisphenol A type polycarbonate, denoted as HBPA-PC-1. The conversion rate of hydrogenated bisphenol A was 96.7%, and the intrinsic viscosity was 0.45 dL / g.

[0041] Infrared data of HBPA-PC-1 (KBr, cm –1 ): 3450br, 2948s, 2845s, 1735s, 1654w, 1593w, 1468s, 1449s, 1388s, 1369s, 1328s, 1251s, 1158w, 1116w, 1075m, 1036s, 1012s, 949s, 930m, 903m, 794w, 763w, 728w, 715w, 658w, see Figure 1 (Instrument model: Nicolet ESP 460)

[0042] 1H NMR data of HBPA-PC-1 1 H NMR (300MHz, CDCl3): 5.67(s,1H), 4.86(s,1H), 4.47(s,1H), 2.09(d,2H), 1.73(d,2H), 1.60(s,2H), 1.33(m,2H), 0.72(s,6H), see Figure 2 (Instrument model: BrukerAVANCE II 300M)

[0043] Example 2

[0044] In a 100 mL three-necked flask equipped with a nitrogen inlet, a by-product distillation outlet, and a mechanical stirrer, hydrogenated bisphenol A (12.02 g, 0.05 mol), diphenyl carbonate (11.25 g, 0.0525 mol), and lithium methoxide (1.9 mg, 0.05 mmol) were added. The reaction mixture was stirred and heated to 210 °C, and reacted under a vacuum of 5 kPa for 1 hour. The temperature was then increased to 230 °C while the vacuum was decreased to 0.1 kPa. The reaction was stopped when the rod-climbing phenomenon occurred, yielding hydrogenated bisphenol A type polycarbonate, denoted as HBPA-PC-2. The conversion rate of hydrogenated bisphenol A was 95.7%, and the intrinsic viscosity was 0.42 dL / g.

[0045] Example 3

[0046] In a 100 mL three-necked flask equipped with a nitrogen inlet, a by-product distillation outlet, and a mechanical stirrer, hydrogenated bisphenol A (12.02 g, 0.05 mol), diphenyl carbonate (11.25 g, 0.0525 mol), and potassium acetate (4.9 mg, 0.05 mmol) were added. The reaction mixture was stirred and heated to 210 °C, and reacted under a vacuum of 5 kPa for 1 hour. The temperature was then increased to 230 °C while the vacuum was decreased to 0.1 kPa. The reaction was stopped when the rod-climbing phenomenon occurred, yielding hydrogenated bisphenol A type polycarbonate, denoted as HBPA-PC-3. The conversion rate of hydrogenated bisphenol A was 95.6%, and the intrinsic viscosity was 0.40 dL / g.

[0047] Example 4

[0048] In a 100 mL three-necked flask equipped with a nitrogen inlet, a by-product distillation outlet, and a mechanical stirrer, hydrogenated bisphenol A (12.02 g, 0.05 mol), diphenyl carbonate (11.25 g, 0.0525 mol), and sodium acetate (4.1 mg, 0.05 mmol) were added. The reaction mixture was stirred and heated to 210 °C, and reacted under a vacuum of 5 kPa for 1 hour. The temperature was then increased to 230 °C while the vacuum was decreased to 0.1 kPa. The reaction was stopped when the rod-climbing phenomenon occurred, yielding hydrogenated bisphenol A type polycarbonate, denoted as HBPA-PC-4. The conversion rate of hydrogenated bisphenol A was 94.5%, and the intrinsic viscosity was 0.40 dL / g.

[0049] Example 5

[0050] In a 100 mL three-necked flask equipped with a nitrogen inlet, a by-product distillation outlet, and a mechanical stirrer, hydrogenated bisphenol A (12.02 g, 0.05 mol), diphenyl carbonate (11.25 g, 0.0525 mol), and lithium acetate (3.3 mg, 0.05 mmol) were added. The reaction mixture was stirred and heated to 210 °C, and reacted under a vacuum of 5 kPa for 1 hour. The temperature was then increased to 230 °C while the vacuum was decreased to 0.1 kPa. The reaction was stopped when the rod-climbing phenomenon occurred, yielding hydrogenated bisphenol A type polycarbonate, denoted as HBPA-PC-5. The conversion rate of hydrogenated bisphenol A was 93.8%, and the intrinsic viscosity was 0.39 dL / g.

[0051] Example 6

[0052] In a 100 mL three-necked flask equipped with a nitrogen inlet, a by-product distillation outlet, and a mechanical stirrer, hydrogenated bisphenol A (12.02 g, 0.05 mol), diphenyl carbonate (11.25 g, 0.0525 mol), and potassium methoxide (0.4 mg, 0.005 mmol) were added. The reaction mixture was stirred and heated to 210 °C, and reacted under a vacuum of 5 kPa for 1 hour. The temperature was then increased to 230 °C while the vacuum was decreased to 0.1 kPa. The reaction was stopped when the rod-climbing phenomenon occurred, yielding hydrogenated bisphenol A type polycarbonate, designated HBPA-PC-6. The conversion rate of hydrogenated bisphenol A was 91.5%, and the intrinsic viscosity was 0.30 dL / g.

[0053] Example 7

[0054] In a 100 mL three-necked flask equipped with a nitrogen inlet, a by-product distillation outlet, and a mechanical stirrer, hydrogenated bisphenol A (12.02 g, 0.05 mol), diphenyl carbonate (11.25 g, 0.0525 mol), and potassium methoxide (1.7 mg, 0.025 mmol) were added. The reaction mixture was stirred and heated to 210 °C, and reacted under a vacuum of 5 kPa for 1 hour. The temperature was then increased to 230 °C while the vacuum was decreased to 0.1 kPa. The reaction was stopped when the rod-climbing phenomenon occurred, yielding hydrogenated bisphenol A type polycarbonate, designated HBPA-PC-7. The conversion rate of hydrogenated bisphenol A was 92.3%, and the intrinsic viscosity was 0.33 dL / g.

[0055] Example 8

[0056] In a 100 mL three-necked flask equipped with a nitrogen inlet, a by-product distillation outlet, and a mechanical stirrer, hydrogenated bisphenol A (12.02 g, 0.05 mol), diphenyl carbonate (11.25 g, 0.0525 mol), and potassium methoxide (7.0 mg, 0.1 mmol) were added. The reaction mixture was stirred and heated to 210 °C, and reacted under a vacuum of 5 kPa for 1 hour. The temperature was then increased to 230 °C while the vacuum was decreased to 0.1 kPa. The reaction was stopped when the rod-climbing phenomenon occurred, yielding hydrogenated bisphenol A type polycarbonate, designated HBPA-PC-8. The conversion rate of hydrogenated bisphenol A was 90.1%, and the intrinsic viscosity was 0.24 dL / g.

[0057] Example 9

[0058] In a 100 mL three-necked flask equipped with a nitrogen inlet, a by-product distillation outlet, and a mechanical stirrer, hydrogenated bisphenol A (12.02 g, 0.05 mol), diphenyl carbonate (11.25 g, 0.0525 mol), and potassium methoxide (17.5 mg, 0.25 mmol) were added. The reaction mixture was stirred and heated to 210 °C, and reacted under a vacuum of 5 kPa for 1 hour. The temperature was then increased to 230 °C while the vacuum was decreased to 0.1 kPa. The reaction was stopped when the rod-climbing phenomenon occurred, yielding hydrogenated bisphenol A type polycarbonate, designated HBPA-PC-9. The conversion rate of hydrogenated bisphenol A was 89.5%, and the intrinsic viscosity was 0.20 dL / g.

[0059] Example 10

[0060] In a 100 mL three-necked flask equipped with a nitrogen inlet, a by-product distillation outlet, and a mechanical stirrer, hydrogenated bisphenol A (12.02 g, 0.05 mol), diphenyl carbonate (10.17 g, 0.0475 mol), and potassium methoxide (3.5 mg, 0.05 mmol) were added. The reaction mixture was stirred and heated to 210 °C, and reacted under a vacuum of 5 kPa for 1 hour. The temperature was then increased to 230 °C while the vacuum was decreased to 0.1 kPa. The reaction was stopped when the rod-climbing phenomenon occurred, yielding hydrogenated bisphenol A type polycarbonate, designated HBPA-PC-10. The conversion rate of hydrogenated bisphenol A was 91.5%, and the intrinsic viscosity was 0.35 dL / g.

[0061] Example 11

[0062] In a 100 mL three-necked flask equipped with a nitrogen inlet, a by-product distillation outlet, and a mechanical stirrer, hydrogenated bisphenol A (12.02 g, 0.05 mol), diphenyl carbonate (10.71 g, 0.05 mol), and potassium methoxide (3.5 mg, 0.05 mmol) were added. The reaction mixture was stirred and heated to 210 °C, and reacted under a vacuum of 5 kPa for 1 hour. The temperature was then increased to 230 °C while the vacuum was decreased to 0.1 kPa. The reaction was stopped when the rod-climbing phenomenon occurred, yielding hydrogenated bisphenol A type polycarbonate, designated HBPA-PC-11. The conversion rate of hydrogenated bisphenol A was 94.6%, and the intrinsic viscosity was 0.41 dL / g.

[0063] Example 12

[0064] In a 100 mL three-necked flask equipped with a nitrogen inlet, a by-product distillation outlet, and a mechanical stirrer, hydrogenated bisphenol A (12.02 g, 0.05 mol), diphenyl carbonate (10.71 g, 0.05 mol), and potassium methoxide (3.5 mg, 0.05 mmol) were added. The reaction mixture was stirred and heated to 210 °C, and reacted under a vacuum of 5 kPa for 1 hour. The temperature was then increased to 230 °C while the vacuum was decreased to 0.1 kPa. The reaction was stopped when the rod-climbing phenomenon occurred, yielding hydrogenated bisphenol A type polycarbonate, designated HBPA-PC-11. The conversion rate of hydrogenated bisphenol A was 94.6%, and the intrinsic viscosity was 0.41 dL / g.

[0065] Example 13

[0066] In a 100 mL three-necked flask equipped with a nitrogen inlet, a by-product distillation outlet, and a mechanical stirrer, hydrogenated bisphenol A (12.02 g, 0.05 mol), diphenyl carbonate (12.32 g, 0.0575 mol), and potassium methoxide (3.5 mg, 0.05 mmol) were added. The reaction mixture was stirred and heated to 210 °C, and reacted under a vacuum of 5 kPa for 1 hour. The temperature was then increased to 230 °C while the vacuum was decreased to 0.1 kPa. The reaction was stopped when the rod-climbing phenomenon occurred, yielding hydrogenated bisphenol A type polycarbonate, designated HBPA-PC-13. The conversion rate of hydrogenated bisphenol A was 91.7%, and the intrinsic viscosity was 0.31 dL / g.

[0067] Example 14

[0068] In a 100 mL three-necked flask equipped with a nitrogen inlet, a by-product distillation outlet, and a mechanical stirrer, hydrogenated bisphenol A (12.02 g, 0.05 mol), diphenyl carbonate (11.25 g, 0.0525 mol), and potassium methoxide (3.5 mg, 0.05 mmol) were added. The reaction mixture was stirred and heated to 210 °C, and reacted under a vacuum of 5 kPa for 0.5 h. The temperature was then increased to 230 °C while the vacuum was decreased to 0.1 kPa. The reaction was stopped when the rod-climbing phenomenon occurred, yielding hydrogenated bisphenol A type polycarbonate, designated HBPA-PC-14. The conversion rate of hydrogenated bisphenol A was 89.3%, and the intrinsic viscosity was 0.36 dL / g.

[0069] Example 15

[0070] In a 100 mL three-necked flask equipped with a nitrogen inlet, a by-product distillation outlet, and a mechanical stirrer, hydrogenated bisphenol A (12.02 g, 0.05 mol), diphenyl carbonate (11.25 g, 0.0525 mol), and potassium methoxide (3.5 mg, 0.05 mmol) were added. The reaction mixture was stirred and heated to 210 °C, and reacted under a vacuum of 5 kPa for 2 hours. The temperature was then increased to 230 °C while the vacuum was decreased to 0.1 kPa. The reaction was stopped when the rod-climbing phenomenon occurred, yielding hydrogenated bisphenol A type polycarbonate, designated HBPA-PC-15. The conversion rate of hydrogenated bisphenol A was 94.3%, and the intrinsic viscosity was 0.37 dL / g.

[0071] Example 16

[0072] In a 100 mL three-necked flask equipped with a nitrogen inlet, a by-product distillation outlet, and a mechanical stirrer, hydrogenated bisphenol A (12.02 g, 0.05 mol), diphenyl carbonate (11.25 g, 0.0525 mol), and potassium methoxide (3.5 mg, 0.05 mmol) were added. The reaction mixture was stirred and heated to 210 °C, and reacted under a vacuum of 5 kPa for 5 hours. The temperature was then increased to 230 °C while the vacuum was decreased to 0.1 kPa. The reaction was stopped when the rod-climbing phenomenon occurred, yielding hydrogenated bisphenol A type polycarbonate, designated HBPA-PC-16. The conversion rate of hydrogenated bisphenol A was 95.8%, and the intrinsic viscosity was 0.31 dL / g.

[0073] Example 17

[0074] In a 100 mL three-necked flask equipped with a nitrogen inlet, a by-product distillation outlet, and a mechanical stirrer, hydrogenated bisphenol A (12.02 g, 0.05 mol), diphenyl carbonate (11.25 g, 0.0525 mol), and potassium methoxide (3.5 mg, 0.05 mmol) were added. The reaction mixture was stirred and heated to 210 °C, and reacted under a vacuum of 5 kPa for 12 hours. The temperature was then increased to 230 °C while the vacuum was decreased to 0.1 kPa. The reaction was stopped when the rod-climbing phenomenon occurred, yielding hydrogenated bisphenol A type polycarbonate, designated HBPA-PC-17. The conversion rate of hydrogenated bisphenol A was 95.7%, and the intrinsic viscosity was 0.30 dL / g.

[0075] Example 18

[0076] In a 100 mL three-necked flask equipped with a nitrogen inlet, a by-product distillation outlet, and a mechanical stirrer, hydrogenated bisphenol A (12.02 g, 0.05 mol), diphenyl carbonate (11.25 g, 0.0525 mol), and potassium methoxide (3.5 mg, 0.05 mmol) were added. The reaction mixture was stirred and heated to 210 °C, and reacted under a vacuum of 50 kPa for 1 hour. The temperature was then increased to 230 °C while the vacuum was decreased to 0.1 kPa. The reaction was stopped when the rod-climbing phenomenon occurred, yielding hydrogenated bisphenol A type polycarbonate, designated HBPA-PC-18. The conversion rate of hydrogenated bisphenol A was 88.5%, and the intrinsic viscosity was 0.28 dL / g.

[0077] Example 19

[0078] In a 100 mL three-necked flask equipped with a nitrogen inlet, a by-product distillation outlet, and a mechanical stirrer, hydrogenated bisphenol A (12.02 g, 0.05 mol), diphenyl carbonate (11.25 g, 0.0525 mol), and potassium methoxide (3.5 mg, 0.05 mmol) were added. The reaction mixture was stirred and heated to 210 °C, and reacted under a vacuum of 20 kPa for 1 hour. The temperature was then increased to 230 °C while the vacuum was decreased to 0.1 kPa. The reaction was stopped when the rod-climbing phenomenon occurred, yielding hydrogenated bisphenol A type polycarbonate, designated HBPA-PC-19. The conversion rate of hydrogenated bisphenol A was 90.5%, and the intrinsic viscosity was 0.35 dL / g.

[0079] Example 20

[0080] In a 100 mL three-necked flask equipped with a nitrogen inlet, a by-product distillation outlet, and a mechanical stirrer, hydrogenated bisphenol A (12.02 g, 0.05 mol), diphenyl carbonate (11.25 g, 0.0525 mol), and potassium methoxide (3.5 mg, 0.05 mmol) were added. The reaction mixture was stirred and heated to 210 °C, and reacted under a vacuum of 5 kPa for 1 hour. The temperature was maintained at 210 °C, and the vacuum was further reduced to 0.1 kPa. The reaction was terminated when the rod-climbing phenomenon occurred, yielding hydrogenated bisphenol A type polycarbonate, designated HBPA-PC-20. The conversion rate of hydrogenated bisphenol A was 91.2%, and the intrinsic viscosity was 0.22 dL / g.

[0081] Example 21

[0082] In a 100 mL three-necked flask equipped with a nitrogen inlet, a by-product distillation outlet, and a mechanical stirrer, hydrogenated bisphenol A (12.02 g, 0.05 mol), diphenyl carbonate (11.25 g, 0.0525 mol), and potassium methoxide (3.5 mg, 0.05 mmol) were added. The reaction mixture was stirred and heated to 210 °C, and reacted under a vacuum of 5 kPa for 1 hour. The temperature was then increased to 240 °C while the vacuum was decreased to 0.1 kPa. The reaction was stopped when the rod-climbing phenomenon occurred, yielding hydrogenated bisphenol A type polycarbonate, designated HBPA-PC-21. The conversion rate of hydrogenated bisphenol A was 94.5%, and the intrinsic viscosity was 0.38 dL / g.

[0083] Example 22

[0084] In a 100 mL three-necked flask equipped with a nitrogen inlet, a by-product distillation outlet, and a mechanical stirrer, hydrogenated bisphenol A (12.02 g, 0.05 mol), diphenyl carbonate (11.25 g, 0.0525 mol), and potassium methoxide (3.5 mg, 0.05 mmol) were added. The reaction mixture was stirred and heated to 210 °C, and reacted under a vacuum of 5 kPa for 1 hour. The temperature was then increased to 250 °C while the vacuum was decreased to 0.1 kPa. The reaction was stopped when the rod-climbing phenomenon occurred, yielding hydrogenated bisphenol A type polycarbonate, designated HBPA-PC-22. The conversion rate of hydrogenated bisphenol A was 92.7%, and the intrinsic viscosity was 0.32 dL / g.

[0085] Implementation column 23 (film thickness: 1mm)

[0086] The prepared hydrogenated bisphenol A type polycarbonate was evenly spread in a 50mm×50mm×1mm mold, with high-temperature resistant PET film placed on both sides of the mold. The mold was then placed flat on a flat vulcanizing machine, with the machine's heating temperature set to 230℃. Once the set temperature was reached, the flat vulcanizing machine was started to raise the heated layer and clamp the mold, resulting in a 1mm thick hydrogenated bisphenol A type polycarbonate film. The HBPA-PC film has a UV-Vis transmittance of 98.2% at 600nm and a refractive index of 1.6385 at 1550nm.

[0087] Hydrogenated bisphenol A type polycarbonate film obtained by hot pressing in a flat vulcanizing machine is shown below. Figure 7 (Specifications: 50mm×50mm×1mm; Model: XKl3-624-0036)

[0088] Example 24 (film thickness: 2mm)

[0089] The prepared hydrogenated bisphenol A type polycarbonate was evenly spread in a 50mm×50mm×2mm mold, with high-temperature resistant PET film placed on both sides of the mold. The mold was then placed flat on a flat vulcanizing machine, with the machine's heating temperature set to 230℃. Once the set temperature was reached, the flat vulcanizing machine was started to raise the heated layer and clamp the mold, resulting in a 2mm thick hydrogenated bisphenol A type polycarbonate film. The HBPA-PC film has a UV-Vis transmittance of 90.5% at 600nm and a refractive index of 1.6045 at 1550nm.

[0090] Implementation column 25 (film thickness: 3mm)

[0091] The prepared hydrogenated bisphenol A type polycarbonate was evenly spread in a 50mm×50mm×3mm mold, with high-temperature resistant PET film placed on both sides of the mold. The mold was then placed flat on a flat vulcanizing machine, with the machine's heating temperature set to 230℃. Once the set temperature was reached, the flat vulcanizing machine was started to raise the heated layer and clamp the mold, resulting in a 3mm thick hydrogenated bisphenol A type polycarbonate film. The HBPA-PC film has a UV-Vis transmittance of 82.5% at 600nm and a refractive index of 1.5806 at 1550nm.

[0092] Implementation of Column 26

[0093] The hydrogenated bisphenol A type polycarbonate in Example 1 was characterized as follows.

[0094] (1) Determination of the molecular weight of HBPA-PC-1

[0095] Take 5.0 mg of HBPA-PC-1, dissolve it in 1 mL of tetrahydrofuran solution, filter it through a polytetrafluoroethylene filter membrane with a pore size of 0.22 μm, and add 20 μL to a Shimadzu (Japan) "LC-20AD GPC" syringe. The weight-average molecular weight is calculated to be 32031 and the molecular weight distribution index is 1.35.

[0096] Test conditions: column temperature 40℃; eluent: tetrahydrofuran; flow rate 0.6 mL / min; detector: RID-10A detector; calibration: molecular weight calibration was performed using four different standard polystyrene with molecular weights ranging from 2,000 to 100,000.

[0097] (2) Characterization of HBPA-PC-1 crystallinity

[0098] The crystallinity of HBPA-PC can be characterized by X-ray powder diffraction. The results show that a relatively wide amorphous envelope appears near a diffraction angle of 18°, indicating that HBPA-PC is amorphous. See Figure 5 Powder diffraction diagram of HBPA-PC-1. (Instrument model: Rigaku D / Max-2500)

[0099] (3) Determination of the glass transition temperature of HBPA-PC-1

[0100] A 5.0 mg sample was placed in an aluminum dish, compressed, sealed, and then added to a PerkinElmer (USA) DSC 8500 differential scanning calorimeter furnace. The calculated glass transition temperature was 180 °C. See [link / reference]. Figure 3 HBPA-PC-1 differential scanning calorimetry curve.

[0101] Test conditions: Heating process: 30~200℃; heating rate: 10℃ / min; hold at 200℃ for 3 minutes; cooling process: 200~30℃; cooling rate: 10℃ / min; hold at 30℃ for 3 minutes; heating process: 30~200℃; heating rate: 10℃ / min.

[0102] (4) Thermal stability characterization of HBPA-PC-1

[0103] The thermal stability of HBPA-PC can be characterized by thermogravimetric analysis. The results show that this material possesses high thermal stability, with a thermal decomposition temperature reaching 310℃, and can remain stable at relatively high temperatures. See [link to relevant documentation]. Figure 4 Thermogravimetric analysis diagram of HBPA-PC-1. (Instrument model: NETZSCH / TG 209F3)

[0104] Test conditions: Heating rate of 10℃ / min.

[0105] (5) Determination of tensile properties of HBPA-PC-1

[0106] The HBPA-PC-1 sample was made into a dumbbell-shaped specimen of 50mm×10mm×2mm and placed in the fixture of the "WDT0.2" electronic universal testing machine made by KELONGLI (China). The tensile strength was calculated to be 15.6MPa and the elongation at break was 8.80%.

[0107] Test conditions: Tensile rate of 10 mm / min.

[0108] (6) Determination of Vicat softening point of HBPA-PC

[0109] The Vicat softening temperature is an indicator for evaluating the heat resistance of materials and reflecting the physical and mechanical properties of products under heated conditions. A higher Vicat softening temperature indicates better dimensional stability and less heat deformation under heat, meaning better resistance to heat deformation. HBPA-PC has a Vicat softening temperature of 152.3℃, exhibiting good dimensional stability. See [link / reference]. Figure 6 Vicat softening point diagrams of HBPA-PC at different intrinsic viscosities. (Instrument model: Microcomputer-controlled heat distortion Vicat softening tester VTM1300-A1)

[0110] Comparative Example 1

[0111] In a 100 mL three-necked flask equipped with a nitrogen inlet, a by-product distillation outlet, and a mechanical stirrer, hydrogenated bisphenol A (12.02 g, 0.05 mol) and diphenyl carbonate (11.25 g, 0.0525 mol) were added without a catalyst. The reaction mixture was stirred and heated to 210 °C and reacted under a vacuum of 5 kPa for 1 hour. The temperature was then increased to 230 °C while the vacuum was decreased to 0.1 kPa. The reaction was stopped when the rod-climbing phenomenon occurred, yielding hydrogenated bisphenol A type polycarbonate, designated HBPA-PC-23. The conversion rate of hydrogenated bisphenol A was 52.6%, and the intrinsic viscosity was 0.16 dL / g.

[0112] Comparative Example 2

[0113] In a 100 mL three-necked flask equipped with a nitrogen inlet, a by-product distillation outlet, and a mechanical stirrer, hydrogenated bisphenol A (12.02 g, 0.05 mol), diphenyl carbonate (11.25 g, 0.0525 mol), and lithium chloride (2.2 mg, 0.05 mmol) were added. The reaction mixture was stirred and heated to 210 °C, and reacted under a vacuum of 5 kPa for 1 hour. The temperature was then increased to 230 °C while the vacuum was decreased to 0.1 kPa. The reaction was stopped when the rod-climbing phenomenon occurred, yielding hydrogenated bisphenol A type polycarbonate, designated HBPA-PC-24. The conversion rate of hydrogenated bisphenol A was 76.7%, and the intrinsic viscosity was 0.23 dL / g.

[0114] Comparative Example 3

[0115] In a 100 mL three-necked flask equipped with a nitrogen inlet, a by-product distillation outlet, and a mechanical stirrer, hydrogenated bisphenol A (12.02 g, 0.05 mol), diphenyl carbonate (11.25 g, 0.0525 mol), and sodium hydroxide (2.0 mg, 0.05 mmol) were added. The reaction mixture was stirred and heated to 210 °C, and reacted under a vacuum of 5 kPa for 1 hour. The temperature was then increased to 230 °C while the vacuum was decreased to 0.1 kPa. The reaction was stopped when the rod-climbing phenomenon occurred, yielding hydrogenated bisphenol A type polycarbonate, designated HBPA-PC-25. The conversion rate of hydrogenated bisphenol A was 79.3%, and the intrinsic viscosity was 0.31 dL / g.

[0116] Comparative Example 4

[0117] In a 100 mL three-necked flask equipped with a nitrogen inlet, a by-product distillation outlet, and a mechanical stirrer, hydrogenated bisphenol A (12.02 g, 0.05 mol), diphenyl carbonate (11.25 g, 0.0525 mol), and stannous octoate (20.3 mg, 0.05 mmol) were added. The reaction mixture was stirred and heated to 210 °C, and reacted under a vacuum of 5 kPa for 1 hour. The temperature was then increased to 230 °C while the vacuum was decreased to 0.1 kPa. The reaction was stopped when the rod-climbing phenomenon occurred, yielding hydrogenated bisphenol A type polycarbonate, designated HBPA-PC-26. The conversion rate of hydrogenated bisphenol A was 60.5%, and the intrinsic viscosity was 0.11 dL / g.

[0118] Comparative Example 5

[0119] In a 100 mL three-necked flask equipped with a nitrogen inlet, a by-product distillation outlet, and a mechanical stirrer, hydrogenated bisphenol A (12.02 g, 0.05 mol), diphenyl carbonate (11.25 g, 0.0525 mol), and potassium methoxide (3.5 mg, 0.05 mmol) were added. The reaction mixture was stirred and heated to 200 °C, and reacted under a vacuum of 5 kPa for 1 hour. The temperature was maintained at 200 °C while the vacuum was reduced to 0.1 kPa. No rod climbing phenomenon occurred, indicating that polycondensation did not occur, and this reaction was designated HBPA-PC-27.

[0120] Comparative Example 6

[0121] In a 100 mL three-necked flask equipped with a nitrogen inlet, a by-product distillation outlet, and a mechanical stirrer, hydrogenated bisphenol A (12.02 g, 0.05 mol), diphenyl carbonate (11.25 g, 0.0525 mol), and potassium methoxide (3.5 mg, 0.05 mmol) were added. The reaction mixture was stirred and heated to 210 °C, and reacted under a vacuum of 5 kPa for 1 hour. The temperature was then increased to 260 °C while the vacuum was decreased to 0.1 kPa. The reaction was stopped when the rod-climbing phenomenon occurred, yielding hydrogenated bisphenol A type polycarbonate, designated HBPA-PC-28. The conversion rate of hydrogenated bisphenol A was 80.5%, and the intrinsic viscosity was 0.31 dL / g. When the temperature was too high, the hydrogenated bisphenol A type polycarbonate underwent decomposition, resulting in a decrease in intrinsic viscosity and molecular weight.

[0122] Comparative Example 7

[0123] In a 100 mL three-necked flask equipped with a nitrogen inlet, a by-product distillation outlet, and a mechanical stirrer, hydrogenated bisphenol A (12.02 g, 0.05 mol), diphenyl carbonate (11.25 g, 0.0525 mol), and potassium methoxide (3.5 mg, 0.05 mmol) were added. The reaction mixture was stirred and heated to 210 °C, and reacted under a vacuum of 30 kPa for 1 hour. The temperature was then increased to 230 °C while the vacuum was decreased to 0.1 kPa. The reaction was stopped when the "stick climbing" phenomenon occurred, yielding hydrogenated bisphenol A type polycarbonate, designated HBPA-PC-29. The conversion rate of hydrogenated bisphenol A was 65.5%, and the intrinsic viscosity was 0.15 dL / g. Excessive esterification vacuum is detrimental to the forward reaction and reduces the conversion rate of hydrogenated bisphenol A.

[0124] Comparative Example 8

[0125] In a 100 mL three-necked flask equipped with a nitrogen inlet, a byproduct distillation outlet, and a mechanical stirrer, hydrogenated bisphenol A (12.02 g, 0.05 mol), diphenyl carbonate (11.25 g, 0.0525 mol), and potassium methoxide (3.5 mg, 0.05 mmol) were added. The reaction mixture was stirred and heated to 210 °C, and reacted under a vacuum of 1 kPa for 1 hour. The temperature was then increased to 230 °C while the vacuum was decreased to 0.1 kPa. After the reaction was complete, hydrogenated bisphenol A type polycarbonate was obtained, designated HBPA-PC-30. During the reaction, it was found that when the esterification vacuum was below 5 kPa, diphenyl carbonate was removed along with the phenol, preventing the reaction from proceeding.

[0126] Comparative Example 9

[0127] In a 100 mL three-necked flask equipped with a nitrogen inlet, a by-product distillation outlet, and a mechanical stirrer, hydrogenated bisphenol A (12.02 g, 0.05 mol), diphenyl carbonate (11.25 g, 0.0525 mol), and potassium methoxide (3.5 mg, 0.05 mmol) were added. The reaction mixture was stirred and heated to 210 °C, and reacted under a vacuum of 5 kPa for 1 hour. The temperature was then increased to 230 °C while the vacuum was decreased to 2 kPa. The reaction was stopped when the "stick climbing" phenomenon occurred, yielding hydrogenated bisphenol A type polycarbonate, denoted as HBPA-PC-31. The conversion rate of hydrogenated bisphenol A was 74.5%, and the intrinsic viscosity was 0.28 dL / g. Excessive vacuum during polycondensation increases the difficulty of polymerization and reduces the intrinsic viscosity and molecular weight of hydrogenated bisphenol A type polycarbonate.

[0128] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the present invention.

Claims

1. A method for preparing high molecular weight hydrogenated bisphenol A type polycarbonate, characterized in that: include, Under a nitrogen atmosphere, hydrogenated bisphenol A, diphenyl carbonate and organic base catalyst were added to the reactor and stirred. During the esterification stage, the temperature was increased and a vacuum was drawn to continuously remove the byproduct phenol. During the polycondensation stage, the temperature was increased and a vacuum was drawn to carry out the polycondensation reaction. After the reaction was completed, the reactor was cooled to obtain hydrogenated bisphenol A type polycarbonate. The organic base catalyst is at least one of potassium methoxide, lithium methoxide, potassium acetate, sodium acetate, and lithium acetate. The esterification stage is heated at 180–210 °C, the polycondensation stage is heated at 210–250 °C, and the vacuum level during the esterification stage is 5–20 kPa; the vacuum level during the polycondensation stage is below 1 kPa. The hydrogenated bisphenol A type polycarbonate has the following structural formula: ; Where n is a positive integer; The hydrogenated bisphenol A type polycarbonate has an intrinsic viscosity of 0.45 dL / g, a weight-average molecular weight of 30,000, a molecular weight distribution of less than 1.5, a tensile strength of 15.6 MPa, and a glass transition temperature of 178 ℃.

2. The preparation method according to claim 1, characterized in that: The molar ratio of hydrogenated bisphenol A to diphenyl carbonate is 1:0.95–1.15; the molar ratio of hydrogenated bisphenol A to catalyst is 1:0.01%–0.5%.

3. The preparation method according to claim 1, characterized in that: The hydrogenated bisphenol A and diphenyl carbonate are used as raw materials to synthesize polycarbonate, and the transesterification reaction time is 0.5 to 12 hours.

4. The preparation method according to claim 1, characterized in that: The stirring speed is 10–500 r / min.

5. Hydrogenated bisphenol A type polycarbonate prepared by the preparation method according to any one of claims 1 to 4.

6. The hydrogenated bisphenol A type polycarbonate as described in claim 5, characterized in that: The film prepared from hydrogenated bisphenol A type polycarbonate has a light transmittance of 98.2% and a refractive index of 1.6385 at a wavelength of 1550 nm.